2010
DOI: 10.1103/physrevb.81.113307
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diamagnetic shift for negative trions in single semiconductor quantum dots

Abstract: We report on the magnetic response of negative trions X − in single self-assembled InAs/GaAs quantum dots. Unlike the conventional quadratic diamagnetic shift for neutral excitons, the observed X − diamagnetic shifts are small and nonquadratic. In particular, we also observed a reversal in sign of the conventional diamagnetic shift. A theoretical analysis indicates that such anomalous behaviors for X − arise from an apparent change in the electron wave function extent after photon emission due to the strong Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 15 publications
1
25
1
Order By: Relevance
“…Paramagnetic regimes have been visible also for QDs of other compounds, i.e. InAs/GaAs (001) [13]. Here, we demonstrated that post-growth TA treatment might be employed to render non-magnetic epitaxial QDs intrinsically magnetic in a controlled manner.…”
mentioning
confidence: 61%
“…Paramagnetic regimes have been visible also for QDs of other compounds, i.e. InAs/GaAs (001) [13]. Here, we demonstrated that post-growth TA treatment might be employed to render non-magnetic epitaxial QDs intrinsically magnetic in a controlled manner.…”
mentioning
confidence: 61%
“…Furthermore, we find a negative diamagnetic coefficient for X + * 3 . This is known as anomalous diamagnetic shift and was observed for negative trions in InAs/GaAs QDs with weakly confined e − in the conduction band (see Supplementary Section IV) 40 . In our QDs, we ascribe the anomalous diamagnetic shift to an initial state which is more localized along x than the remaining hole after recombination.…”
Section: B Magneto-optical Properties Of Gaas Qdsmentioning
confidence: 73%
“…In the initial state of the CX transition, the hole binds the electron to the QD. In contrast, after recombination of the CX, the remaining electron is less tightly bound to the QD and its wave function spreads into the QD barriers, which results in the observed reduction of γ for CX [49,50]. Technically, the latter argumentation holds for a positive (hole charged) CX as well.…”
Section: -5mentioning
confidence: 86%